Gerenciamento de resíduos com risco biológico e perfurocortantes: conhecimento e sua aplicação no ciclo básico e na pesquisa do Instituto de Ciências Biológicas da UFMG - Monica Maria Campolina Teixeira Stehling (2009)
A quali-quantitative study on knowledge and practice of the waste management activities of the Group A with biological and infectious risk and Group E with perforating, cutting and scarification risk held at the Institute of Biological Sciences at the Federal University of Minas Gerais (UFMG) in 2008 and 2009. The aims of the study were to identify the knowledge of the studied community of the waste management, considering all stages from generation to final disposal and to identify the application of this knowledge in the practices of appropriate waste management in the research laboratories, following its steps according to the current Brazilian laws. Had been serarched professors, graduate and undergraduate students, beneficiary students and staff. Structured questionnaires applied to the undergraduate students, and semi-structured ones to professors, staff, postgraduate and beneficiary students. The method of frequency and proportion was used, the database was built in Epi-Data 3.1 and exported to Excel. A lack of knowledge on the subject was noticed, as well as a commitment and concern of the community involved in the research. The detailed approach on the subject was explicitly raised by all categories including the undergraduate students, as well as professors, beneficiary students and staff who work in research labs. Many of the gaps found are linked to disinformation. It obvious that the lack of institutional investment to provide material and equipments necessary for the implementation of waste management creates a degree of helplessness in the studied community for the application of existing knowledge in the practice of the management of the waste